ANALISIS PENGARUH MOTIVASI DAN STRATEGI PENGELOLAAN TERHADAP OPERASIONAL HOMESTAY DIKABUPATEN KARO - Muhammad Halfi Indra Syahputra (Jurnal Ilmiah Akomodasi Agung, 2020)
The purpose of this study is to determine and analyze the effect of employee motivation on the strategies of homestay operations and the work abilities of employees. This research uses a quantitative approach, namely by using a questionnaire. quantitative, namely by using multiple linear regression analysis with the T test, F test. .